30.4k views
1 vote
1-36. George was solving the equation (2x-1)(x+3)=4 and he got the solutions x=12 and x=-3.Jeffrey came along and said, “You made a big mistake! You set each factor equal to zero, but it'snot equal to zero, it's equal to 4. So you have to set each factor equal to 4 and then solve." Who iscorrect? Show George and Jeffrey how to solve this equation. To be sure that you are correct,check your solutions. Homework Help

User Tom Savage
by
5.6k points

1 Answer

7 votes

Answer:

The solutions are -7/2 and 1. Jeffrey is correct.

Explanation:

We have to use the Bhaskara formula to solve this question.

Bhaskara formula:

Suppose we have the following second order equation:

ax² + bx + c = 0

The solution of the equation are:


x=(-b\pm√(b^2-4ac))/(2a)

In this question:

(2x - 1)(x + 3) = 4

We have to apply the distributive property to place the equation in the correct format to apply Bhaskara.

(2x - 1)(x + 3) = 4

2x² + 6x - x - 3 = 4

2x² + 5x - 3 - 4 = 0

2x² + 5x - 7 = 0


x=(-5\pm√((5)^2-4\ast2\ast(-7)))/(2\ast2)=(-5\pm√(25+56))/(4)=(-5\pm√(81))/(4)=(-5\pm9)/(4)

The solutions are:


x^{^(\prime)}=(-5+9)/(4)=1
x^{^(\prime\prime)}=(-5-9)/(4)=-(14)/(4)=-(7)/(2)

The solutions are -7/2 and 1. Jeffrey is correct.

User Ade
by
5.4k points